2009
DOI: 10.1002/ptr.2805
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Echinacea purpurea (L.) Moench extract on experimental prostate hyperplasia

Abstract: The aim of this study was to examine the effect of purple coneflower (Echinacea purpurea L. Moench) on the prostate gland of rats using an experimental model of benign prostate hyperplasia (BPH). The animals were administered 50 mg/kg of extract preparation for 4 and 8 weeks and the prostate mass and structural degenerative changes were evaluated in the course of the experiment. The administration of E. purpurea extract to rats with hyperplasia for 4 and 8 weeks gradually and significantly reduced the prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Skaudickas et al (2003) observed significant elevation in the number of lymphocytes in rat receiving E. purpurea extract for at least 8 weeks. Improvement in feed conversion was reported by Maass et al (2005) in pig receiving E. purpurea cobs supplementation for at least two weeks.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Skaudickas et al (2003) observed significant elevation in the number of lymphocytes in rat receiving E. purpurea extract for at least 8 weeks. Improvement in feed conversion was reported by Maass et al (2005) in pig receiving E. purpurea cobs supplementation for at least two weeks.…”
Section: Introductionmentioning
confidence: 76%
“…It could increase the number of lymphocytes too. However, elevation in the number of lymphocytes can be statistically reliable only if rats are fed Echinacea for at least eight weeks (Skaudickas et al, 2003). ND and AI HI-antibody titers were routinely examined to evaluate the effect of E. purpurea on humoral immune response of the chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, phytotherapeutics has become popular in the treatment of BPH. Several plants, including Sphaeranthus indicus, Echinacea purpurea and Roystonea regia have been reported to possess anti-BPH potential (Skaudickas et al, 2009;Nahata and Dixit, 2011;Emeka and Obidoa, 2009). The employment of S. macrocarpon in ethnomedicine to manage inflammatory tumors motivated us to study its effects on BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Serenoa repens [2930] Ganoderma lucidum ,[31] Lepidium meyenii (Red Maca),[32] banana peel,[33] and Echinacea purpurea [34] showed significant improvements of BPH. The results obtained in this study could have successfully presented that K. parviflora is a novel entry from Zigiberaceae plant and K. parviflora would be a promising candidate.…”
Section: Results and Methodsmentioning
confidence: 99%